The imitative phase of intellectual development - Neiman, Ruth Emma (My University, 1906)
Introduction: Of the many forces which tend to bring about the development of the human mind, imitation is perhaps one of the strongest. The word “imitation” carries with it a variety of meanings. And yet, strange as it may seem, there is always a common impression or idea conveyed when it is used. Recent psychological investigation has brought out many important facts concerning this commonly used expression “imitation.” A deeper, broader meaning has been applied, a knowledge of which would prove valuable to anyone who has to do with the training of an undeveloped mind. In order to enter into a discussion of imitation from a psychological point of view it is necessary to make a clear distinction between two kinds of imitation.
Citation: Neiman, Ruth Emma. The imitative phase of intellectual development. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Intellectual Development; Psychology; Imitation; Theses; Manuscripts (documents)